Scimitar syndrome, bronchiectasis, haemoptysis and a pneumonectomy - Emma Jeffs; Hyukjoon Lee; Lutz Beckert (Respirology Case Reports, 2024)
Abstract Scimitar syndrome is a rare condition characterized by partial or complete anomalous pulmonary venous drainage of the lung to the inferior vena cava, right lung hypoplasia and dextroposition of the heart. Haemoptysis is uncommon in adults, although the clinical spectrum is wide. We report a case of a 38‐year‐old male with scimitar syndrome who had low grade haemoptysis persisting over several years secondary to bronchiectatic changes in his hypoplastic right lung. Conservative measures to manage haemoptysis were unsuccessful and the patient proceeded to bronchial artery embolization. The post‐procedure course was complicated by lung infarction and the patient ultimately required pneumonectomy. Deformities of the blood vessels and lungs are complex in scimitar syndrome. Bronchial artery embolization should be approached cautiously to protect pulmonary perfusion.